Visual-inertial navigation assisted by a single UWB anchor with an unknown position - Haolong Luo; Danping Zou; Jiansheng Li; Ancheng Wang; Li Wang; Zidi Yang; Guangyun Li (Satellite Navigation)
Abstract Navigation technology, which integrates vision, Inertial Measurement Unit (IMU), and Ultra-Wideband (UWB) sensors in GNSS-denied environments has gained a significant attention. However, inaccurate estimation of UWB anchor positions and improper sensor weighting among heterogeneous sensors significantly impairs the positioning accuracy and robustness of Visual-Inertial-UWB (VIU) systems. To accurately and rapidly estimate the UWB anchor positions, we employed the robust ridge nonlinear least-squares method to improve the accuracy and reliability of the estimated UWB anchor position. Additionally, we proposed a simple and effective method to assess the accuracy of the UWB anchor position using the geometric dilution precision principle, which facilitates rapid and accurate estimation of the UWB anchor position. Furthermore, we designed a method to calculate the estimated UWB anchor position error in real-world settings. Finally, we proposed a nonlinear optimization method with dynamically adaptive weighting based on the HELMERT variance component estimation principle, which assigns appropriate weights to heterogeneous sensors. To validate the feasibility and effectiveness of the proposed method, comprehensive simulations and real-world experiments were conducted. First, using Monte Carlo simulation and real-world experiments, we validated the effectiveness of the proposed methods for UWB anchor position and its accuracy estimation. Then, we conducted ablation experiments utilizing the open-source VIRAL and real-world datasets. The experimental results demonstrate that the proposed method exhibits superior positioning accuracy and robustness in contrast to the open-source VINS-MONO and VIR-SLAM methods.